Optimizing Osseodensification Drilling for Dental Implant Placement: An In Vitro Study - Xingru Tao; Jie Yang; Tai Ma; Ming Chen; Qinglong An; Dedong Yu (Clinical and Experimental Dental Research)
ABSTRACT Objectives This study aims to optimize the parameters of osseodensification drilling (OD) to improve the primary stability of dental implants in low‐density bone. Material and Methods Polyurethane foam blocks (PFB) of 0.160 g/cm3 were used to simulate low‐density bone (Type IV bone). Two drills, i.e., bone level tapered drills and Densah drills, were used in conventional drilling (CD) and OD, respectively. Drilling was performed on a DMU machine, varying spin speed, feed per tooth, and irrigation with or without 4°C saline. Thrust force, temperature, and entrance characteristics of implant sites in CD and OD were compared. The primary stability of implants was assessed via insertion torque (IT), removal torque (RT), and implant stability quotient (ISQ). Results OD demonstrated higher thrust force than CD with maximum values at 300 rpm (2.99 ± 0.22 N vs. 2.77 ± 0.17 N, p < 0.01). Temperature elevation was lower in OD than that in CD under irrigation (3.35°C vs. 4.67°C). Despite comparable ISQ values (CD: 46.71 ± 8.56 vs OD: 47.08 ± 5.95, p = 0.86), OD achieved higher IT (11.73 ± 0.45 N·m vs. 7.77 ± 0.21 N·m, p < 0.001) and higher RT (9.28 ± 0.45 N·m vs. 6.65 ± 0.19 N·m, p < 0.001). Morphological analysis revealed fewer defects (tears/potholes) in OD than CD. Conclusions OD drills may avoid iatrogenic damage of the morphology of implant sites and enhance primary stability in Type IV bone at 1500 rpm and 0.04 mm/z with irrigation to prevent thermal damage. OD also outweights CD in increased bone density, thrust force, and torque. Clinical Implications For Type IV alveolar bone, OD at 1500 rpm and 0.04 mm/z is recommended for improving he primary stability of dental implants. Sufficient irrigation is crucial in both CD and OD for circumventing the thermal damage to bone.